Fingolimod efficacy in multiple sclerosis associated with Sjogren syndrome. (February 2015) - Signoriello, E.; Sagliocchi, A.; Fratta, M.; Lus, G.
<x xml:space="preserve">Abstract</x> Background Sjogren syndrome (SS) is a common autoimmune disease characterized by lymphocytic infiltration of the exocrine glands with neurological involvement in about 20% of patients. The neurological manifestations in the central nervous system CNS may vary and include a multiple sclerosis (MS)‐like disease, and the treatments with immunosuppressive drugs have been undertaken. Case presentation We describe a case of 40‐year‐old woman with clinical and instrumental evidence of an MS characterized by numerous relapses and demyelinating lesions prevailing in the infratentorial and spinal cord. Immunological analysis showed biological data that were consistent with an SS. The treatment with fingolimod showed not only an optimal response to the demyelinating events but also biological parameters. Conclusion These data allow us to hypothesize possible combined efficacy of treatment with fingolimod in SS associated with definite MS.